![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) x/7 = 6/21
x/7 = 2/7
=>x=2
b)2/3x -1/2=1/10
2/3x = 1/10+1/2
2/3x = 3/5
x=3/5:2/3
x=9/10
c)1/4+1/3 : x = -5
d)3x+17=2
đ)2/3x +1/4 =7/12
2x+3/10= 11/6 . 6/11
x : 4 1/3 = -2,5
![](https://rs.olm.vn/images/avt/0.png?1311)
c)
\(4\left(3x-4\right)-2=18\)
<=> \(12x-16-2=18\)
<=> \(12x=36\)
<=> \(x=3\)
Vậy x=3
d)
\(\left(3x-10\right):10=50\)
<=> \(3x-10=500\)
<=> \(3x=510\)
<=> x= \(170\)
Vậy x= 170
f)
\(x-\left[42+\left(-25\right)\right]=-8\)
<=> \(x-17=-8\)
<=> x= \(9\)
Vậy x=9
h)
\(x+5=20-\left(12-7\right)\)
<=> \(x+5=15\)
<=> \(x=10\)
Vậy x= 10
k)
\(\left|x-5\right|=7-\left(-3\right)\)
<=> \(\left|x-5\right|=10\)
* Với \(x>=5\) ; ta được:
\(x-5=10\)
<=> x= 15 (thoả mãn điều kiện )
*Với \(x< 5\) ; ta được:
\(-\left(x-5\right)=10\)
<=> \(-x+5=10\)
<=> \(-x=5\)
<=> \(x=-5\) (thoả mãn điều kiện)
Vậy x=15 ; x= -5
i)
\(\left|x-5\right|=\left|7\right|\)
<=> \(\left|x-5\right|=7\)
*Với \(x>=5\) ; ta được:
\(x-5=7\)
<=> \(x=12\) (thoả mãn)
*Với \(x< 5\) ; ta được:
\(-\left(x-5\right)=7\)
<=> \(-x=2\)
<=> \(x=-2\) (thoả mãn)
Vậy x= 12; x= -2
m)
\(2^{x+1}.2^{2009}=2^{2010}\)
<=> \(2^{x+1+2009}=2^{2010}\)
<=> \(2^{x+2010}=2^{2010}\)
=> \(x+2010=2010\)
=> \(x=0\)
Vậy x=0
n)
\(10-2x=25-3x\)
<=>\(x=15\)
Vậy x=15
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(\dfrac{2}{3}x-\dfrac{1}{2}=\dfrac{1}{10}\)
nên \(\dfrac{2}{3}x=\dfrac{1}{10}+\dfrac{1}{2}=\dfrac{6}{10}=\dfrac{3}{5}\)
hay \(x=\dfrac{3}{5}:\dfrac{2}{3}=\dfrac{9}{10}\)
b: \(\Leftrightarrow5-\dfrac{4}{7}x=13\)
nên 4/7x=-8
hay x=-12
c: \(\left(x+\dfrac{1}{2}\right)\cdot\left(\dfrac{2}{3}-2x\right)=0\)
=>x+1/2=0 hoặc 2/3-2x=0
=>x=-1/2 hoặc x=1/3
d: \(\dfrac{2}{3}x-\dfrac{1}{2}x=\dfrac{5}{12}\)
nên 1/6x=5/12
hay x=5/2
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\dfrac{2}{3}x-\dfrac{3}{2}x=\dfrac{5}{12}\)
\(x\left(\dfrac{2}{3}-\dfrac{3}{2}\right)=\dfrac{5}{12}\)
\(x\cdot\left(-\dfrac{5}{6}\right)=\dfrac{5}{12}\)
\(x=\dfrac{5}{12}:\left(-\dfrac{5}{6}\right)\)
\(x=-\dfrac{1}{2}\)
Vậy \(x=-\dfrac{1}{2}\).
b) \(\dfrac{2}{5}+\dfrac{3}{5}\cdot\left(3x-3\cdot7\right)=-\dfrac{53}{10}\)
\(\dfrac{3}{5}\left(3x-3\cdot7\right)=-\dfrac{53}{10}-\dfrac{2}{5}\)
\(\dfrac{3}{5}\left(3x-3\cdot7\right)=-\dfrac{57}{10}\)
\(3x-3\cdot7=-\dfrac{57}{10}:\dfrac{3}{5}\)
\(3x-3\cdot7=-\dfrac{19}{2}\)
\(3x-21=-\dfrac{19}{2}\)
\(3x=-\dfrac{19}{2}+21\)
\(3x=\dfrac{23}{2}\)
\(x=\)\(\dfrac{23}{2}:3\)
\(x=\dfrac{23}{6}\)
Vậy \(x=\dfrac{23}{6}\).
c) \(\dfrac{7}{9}:\left(2+\dfrac{3}{4x}\right)+\dfrac{5}{3}=\dfrac{23}{27}\)
\(\dfrac{7}{9}:\left(2+\dfrac{3}{4x}\right)=\dfrac{23}{27}-\dfrac{5}{3}\)
\(\dfrac{7}{9}:\left(2+\dfrac{3}{4x}\right)=-\dfrac{22}{27}\)
\(2+\dfrac{3}{4x}=\dfrac{7}{9}:-\dfrac{22}{27}\)
\(2+\dfrac{3}{4x}=-\dfrac{21}{22}\)
\(\dfrac{3}{4x}=-\dfrac{21}{22}-2\)
\(\dfrac{3}{4x}=-\dfrac{65}{22}\)
\(4x=\dfrac{3\cdot22}{-65}\)
\(4x=-\dfrac{66}{65}\)
\(x=-\dfrac{66}{65}:4\)
\(x=-\dfrac{33}{130}\)
Vậy \(x=-\dfrac{33}{130}\).
d) \(-\dfrac{2}{3}x+\dfrac{1}{5}=\dfrac{3}{10}\)
\(-\dfrac{2}{3}x=\dfrac{3}{10}-\dfrac{1}{5}\)
\(-\dfrac{2}{3}x=\dfrac{1}{10}\)
\(x=\dfrac{1}{10}:-\dfrac{2}{3}\)
\(x=-\dfrac{3}{20}\)
Vậy \(x=-\dfrac{3}{20}\).
e) \(\left|x\right|-\dfrac{3}{4}=\dfrac{5}{3}\)
\(\left|x\right|=\dfrac{5}{3}+\dfrac{3}{4}\)
\(\left|x\right|=\dfrac{29}{12}\)
\(x=\dfrac{29}{12}\) hoặc \(=-\dfrac{29}{12}\)
Vậy \(x\in\left\{\dfrac{29}{12};-\dfrac{29}{12}\right\}\).
![](https://rs.olm.vn/images/avt/0.png?1311)
A=-(3x+7)+(5x-2)+(2x-10)
=-3x-7+5x-2+2x-10
=(-3x+5x+2x)-(7+2+10)
=4x-19
B = (6x+8)-(4x-5)-3x
= 6x+8-4x+5-3x
= (6x-4x-3x) + (8+5)
= -x + 13
= 13-x
C = 2(5x+3) - (2x-1) + 12
= 10x+6 - 2x + 1 + 12
= (10x-2x) + (6+1+12)
= 8x + 19
D = (x+7)-3(x+1)+2x-5
= x+7-3x-3+2x-5
= (x-3x+2x) + (7-3-5)
= -1
![](https://rs.olm.vn/images/avt/0.png?1311)
Trl:
\(\left(3x-2^4\right).7^{10}=2.7^{10}\)
\(\Rightarrow\left(3x-16\right)=2.7^{10}:7^{10}\)
\(\Rightarrow\left(3x-16\right)=2.1\)
\(\Rightarrow\left(3x-16\right)=2\)
\(\Rightarrow3x=16+2\)
\(\Rightarrow3x=18\)
\(\Rightarrow x=18:3\)
\(\Rightarrow x=6\)
Hc tốt
\(\left(3x-2^4\right)\times7^{10}=2\times7^{10}\)
\(3x-2^4=2\times7^{10}:7^{10}\)
\(3x-2^4=2\times1\)
\(3x-16=2\)
\(3x=18\)
\(x=6\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a)
\(3x\left(x+1\right)-6\left(x+1\right)=0\\ \Leftrightarrow\left(x+1\right)\left(3x-6\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x=-1\\x=2\end{matrix}\right.\)
b)
\(2x+25-2\left(10-3x\right)=0\\ \Leftrightarrow8x+5=0\\ \Leftrightarrow x=-\dfrac{5}{8}\)
c)
\(\left|x-3\right|=7-\left(-2\right)\\ \Rightarrow\left|x-3\right|=9\\ \Rightarrow\left[{}\begin{matrix}x=12\\x=-6\end{matrix}\right.\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a; -2\(x\) - 3.(\(x-17\)) = 34 - 2.( - \(x\) + 25)
- 2\(x\) - 3\(x\) + 51 = 34 + 2\(x\) - 50
2\(x\) + 2\(x\) + 3\(x\) = - 34 + 50 + 51
7\(x\) = 67
\(x\) = 67 : 7
\(x\) = \(\dfrac{67}{7}\)
Vậy \(x\) = \(\dfrac{67}{7}\)
b; 17\(x\) + 3.(- 16\(x\) - 37) = 2\(x\) + 43 - 4\(x\)
17\(x\) - 48\(x\) - 111 = 2\(x\) - 4\(x\) + 43
- 31\(x\) - 2\(x\) + 4\(x\) = 111 + 43
- \(x\) x (31 + 2 - 4) = 154
- \(x\) x (33 - 4) = 154
- \(x\) x 29 = 154
- \(x\) = 154 : (-29)
\(x\) = - \(\dfrac{154}{29}\)
Vậy \(x=-\dfrac{154}{29}\)
`3x+2.(-7)=10`
`=>3x-14=10`
`=>3x=10+14=24`
`=>x=24:3`
`=>x=8`
a) 3x + 2 . ( -7 ) = 10
3x - 14 = 10
3x = 10 + 14 = 24
x = 24 : 3
x = 8